Accounting Principles for Management: An Introduction (Book). - Dominak, Geraldine F.; Czarsty, Steven L. (The Accounting Review, 1976)
Reviews the book "Accounting Principles for Management: An Introduction," 2nd. ed., by Robert E. Seiler.